GREEN FOOD MARKETING AND LOCAL EMPOWERMENT: BRANDING THE LOCAL ECONOMY THROUGH THE FREE NUTRITIOUS MEAL PROGRAM - Indra Welly Arifin; Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the role of green food marketing in the Free Nutritious Meal Program (MBG) as an instrument for improving community nutrition while empowering the local economy. The study used a descriptive qualitative approach with a literature review of various studies related to MBG, green marketing, MSMEs, and the latest local food innovations (2020–2025). The results show that the integration of green food marketing principles, product and packaging innovation, and digital transformation can increase the added value, image, and branding of the local economy. MBG not only ensures nutritional fulfillment for schoolchildren, toddlers, and pregnant women but also strengthens MSMEs, farmers, and local businesses through a sustainable supply chain. The developed integrative conceptual model combines nutritional fulfillment, economic empowerment, green marketing, and digitalization, thus creating synergy between public health, local economic growth, and environmental sustainability. These findings serve as the basis for recommendations for the government and stakeholders in optimizing MBG as a holistic and sustainable local development strategy.